Optimizing the role of teachers in overcoming student dysgraphia: Neurological study of fine motor developments - Aulia, Nadia; Rudini, Moh.; Mustakim, Mustakim; Motoh, Theopilus C. (Institute of Computer Science (IOCS), 2025)
Students with dysgraphia symptoms often have difficulty in writing due to their lack of fine motor skills, which affects how they write neatly and coordinate information. This study aims to analyze how teachers can help students with dysgraphia, particularly in developing fine motor skills, as well as finding supporting and inhibiting factors in their learning process. With a qualitative phenomenological approach through interviews, observations, and documentation, the results show that the role of teachers as educators and mentors is optimal. Teachers can identify students' problems and design appropriate learning. In addition, collaboration between teachers, parents and schools is an important factor in providing consistent support. The implications of this study show the importance of teacher training to recognize and treat dysgraphia, the use of technology to assist writing, and close cooperation with parents. Developing individualized learning programs and creating a supportive learning environment can also help students with dysgraphia develop optimal writing and learning skills.